2017
DOI: 10.1016/j.taap.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of Septin9 mediated by DNMT3a enhances hepatic stellate cells activation and liver fibrogenesis

Abstract: Liver fibrosis, resulting from chronic and persistent injury to the liver, is a worldwide health problem. Advanced liver fibrosis results in cirrhosis, liver failure and even hepatocellular cancer (HCC), often eventually requiring liver transplantation, poses a huge health burden on the global community. However, the specific pathogenesis of liver fibrosis remains not fully understood. Numerous basic and clinical studies have provided evidence that epigenetic modifications, especially DNA methylation, might co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 78 publications
(83 reference statements)
1
33
0
Order By: Relevance
“…Furthermore, different septin members might have different biological function. It has been reported that SEPT4 and SEPT9 were remarkably downregulated in HSC activation and liver fibrosis; loss-of-SEPT4 exacerbated liver fibrosis [26], and SEPT9 contributed to alleviate liver fibrosis partially through promoting activated HSCs apoptosis [27]. Taken together, we demonstrated for the first time that SEPT6 promotes HSCs activation, proliferation, cell cycle progression, migration, and survival, likely by activating the TGF-β1/Smad, MAPK, and PI3K/AKT signaling pathways.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Furthermore, different septin members might have different biological function. It has been reported that SEPT4 and SEPT9 were remarkably downregulated in HSC activation and liver fibrosis; loss-of-SEPT4 exacerbated liver fibrosis [26], and SEPT9 contributed to alleviate liver fibrosis partially through promoting activated HSCs apoptosis [27]. Taken together, we demonstrated for the first time that SEPT6 promotes HSCs activation, proliferation, cell cycle progression, migration, and survival, likely by activating the TGF-β1/Smad, MAPK, and PI3K/AKT signaling pathways.…”
Section: Discussionsupporting
confidence: 52%
“…This finding implies that SEPT6 plays tissue-specific roles. SEPT4 and SEPT9 have been shown to be decreased following HSCs activation, and the loss of SEPT4 and SEPT9 exacerbates liver fibrosis [26,27]. We detect the level of the entire septins member in healthy and fibrotic rat liver and find that the SEPT6 is elevated significantly.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, TGF‐β1 promoted the expression of DNMT1 and DNMT3A, especially DNMT3A, which suggests that TGF‐β1 plays a certain role in the regulation of EYA4 expression in ESCC. In other human malignancies, TGF‐β1 has also been found to affect transcription and expression of downstream target genes via the regulation of DNMT expression . In ovarian cancer cells, TGF‐β1 induced the expression of DNMT and led to extensive genomic hypermethylation, which influenced the transcription of EMT‐related genes and promoted the EMT process .…”
Section: Discussionmentioning
confidence: 99%
“…In other human malignancies, TGF-b1 has also been found to affect transcription and expression of downstream target genes via the regulation of DNMT expression. [35][36][37] In ovarian cancer cells, TGF-b1 induced the expression of DNMT and led to extensive genomic hypermethylation, which influenced the transcription of EMT-related genes and promoted the EMT process. 38 In hepatocellular carcinoma, TGF-b1 transformed HCC cells into cells with a spindle-shaped morphology, which was accompanied by hypermethylation of CDH1 and the methylation of its promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Septins are a group of GTPase proteins that play a role in cytoskeleton organisation through their links with microtubules and actin filaments (78). Although some septins are associated with the advancement of kidney fibrosis (78), SEPTIN9 specifically has been implicated in a host of disease pathologies, such as prostate cancer (79), colorectal cancer (80), liver fibrosis (81) and T2DM (82). Moreover, SEPTIN9 overexpression has been shown to promote kidney epithelial cell migration (83).…”
Section: Discussionmentioning
confidence: 99%